Novel mechanism of regulation of fibrosis in kidney tumor with tuberous sclerosis - Liang, Sitai (BioMed Central, 2013)
BACKGROUND: Deficiency in tuberin results in activation the mTOR pathway and leads to accumulation of cell matrix proteins. The mechanisms by which tuberin regulates fibrosis in kidney angiomyolipomas (AMLs) of tuberous sclerosis patients are not fully known. METHOD: In the present study, we investigated the potential role of tuberin/mTOR pathway in the regulation of cell fibrosis in AML cells and kidney tumor tissue from tuberous sclerosis complex (TSC) patients. RESULTS: AML cells treated with rapamycin shows a significant decrease in mRNA and protein expression as well as in promoter transcriptional activity of alpha-smooth muscle actin (α-SMA) compared to untreated cells. In addition, cells treated with rapamycin significantly decreased the protein expression of the transcription factor YY1. Rapamycin treatment also results in the redistribution of YY1 from the nucleus to cytoplasm in AML cells. Moreover, cells treated with rapamycin resulted in a significant reduce of binding of YY1 to the αSMA promoter element in nuclear extracts of AML cells. Kidney angiomyolipoma tissues from TSC patients showed lower levels of tuberin and higher levels of phospho-p70S6K that resulted in higher levels of mRNA and protein of αSMA expression compared to control kidney tissues. In addition, most of the α-SMA staining was identified in the smooth muscle cells of AML tissues. YY1 was also significantly increased in tumor tissue of AMLs compared to control kidney tissue suggesting that YY1 plays a major role in the regulation of αSMA. CONCLUSIONS: These data comprise the first report to provide one mechanism whereby rapamycin might inhibit the cell fibrosis in kidney tumor of TSC patients.